The role of family on children's education: Islamic law perspective - Zainudin, Ahmad; Al-Muqri, Fatima (AS-SAKINAH, 2024)
This research examines the role of the family in children's education from the perspective of Islamic law. The main issues raised are how the family influences the process of child education in accordance with the principles of Islamic law and what challenges are faced in its implementation. The purpose of this study is to analyze the role of the family in children's education and how Islamic law governs family responsibilities.. The research method used is literature reviewand in-depth interviews with parents and educators. Data were collected from relevant primary and secondary sources, including classical and contemporary texts on Islamic law and education. The results show that the family has a central role in children's education according to Islamic law, which includes the responsibility to provide adequate religious education, educate children with moral values, and support their academic development. The research found that despite the important role families play, challenges include a lack of understanding of the principles of Islamic law and limited resources. The findings emphasize the need for a more integrative approach and support for families in carrying out their role in children's education in accordance with Islamic law.